SISTEM INFORMASI SD NEGERI 79/IV KOTA JAMBI BERBASIS WEBSITE - Maharani, Lisa; -, Afrizal (JURNAL AKADEMIKA, 2024)
Elementary schools are social institutional units that are given the mandate and task to provide basic education systematically for children aged 6 to 12 years or what is usually called the intellectual period. Elementary school teaches children to become people with character, excel in achievement, have self-confidence, humility and have a quick mind in learning, learn to be friendly with everyone around them. SD Negeri 79/IV Jambi City is one of the educational units under the auspices of the Jambi City Education Office. The aims and objectives of this Skirpsi research are to produce information system software for SD Negeri 79/IV Jambi City. At the system design stage, use Php as the interface design. With the Information System at SD Negeri 79/IV Jambi City, it can provide information relating to SD Negeri 79/IV Jambi City to the entire wider community, especially information regarding New Student Registration, reducing difficulties and time spent searching for data. students, teachers and PPDB data. The Information System for SD Negeri 79/IV Jambi City was created using MySQL for database processing. The input, process and output in this research are student, teacher, news, class, schedule, admin, extracurricular and ppdb data input. The process carried out is student, teacher, news, class, schedule, admin, extracurricular and ppdb and output. generated, namely student data reports, teacher reports and PPDB reports. And it is hoped that this application can be developed further, so that the design will appear more attractive and, it is hoped that the development of the SD Negeri 79/IV information system will be more complex and can provide even better results.